2021
DOI: 10.1038/s42003-021-02490-7
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic stabilization of a double mutant in chymotrypsin inhibitor 2 from a library screen in E. coli

Abstract: Most single point mutations destabilize folded proteins. Mutations that stabilize a protein typically only have a small effect and multiple mutations are often needed to substantially increase the stability. Multiple point mutations may act synergistically on the stability, and it is often not straightforward to predict their combined effect from the individual contributions. Here, we have applied an efficient in-cell assay in E. coli to select variants of the barley chymotrypsin inhibitor 2 with increased sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…We performed the simulations using the Amber a99SB- disp force field with the TIP4P-D-based a99SB- disp water model . Crystal structures of the CI2 WT (PDB: 7A1H) and its mutated variants L49I (PDB: 7AOK), I57V (PDB: 7A3M), and L49I/I57V (PDB: 7AON) were used as the starting conformations for the simulations . The proteins were placed in a cubic box with a volume of 30.66 nm 3 (resulting in a 0.5 nm distance from the protein to all box edges) and solvated with 6728 to 6836 water molecules.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed the simulations using the Amber a99SB- disp force field with the TIP4P-D-based a99SB- disp water model . Crystal structures of the CI2 WT (PDB: 7A1H) and its mutated variants L49I (PDB: 7AOK), I57V (PDB: 7A3M), and L49I/I57V (PDB: 7AON) were used as the starting conformations for the simulations . The proteins were placed in a cubic box with a volume of 30.66 nm 3 (resulting in a 0.5 nm distance from the protein to all box edges) and solvated with 6728 to 6836 water molecules.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…We recently showed that L49I destabilizes the folded state of CI2 (ΔΔ G f = 3.4 ± 0.1 kJ/mol), while I57V stabilizes it slightly (ΔΔ G f = −2.2 ± 0.1 kJ/mol) . Notably, the double mutant (L49I/I57V) is significantly more stable than either of the single mutants (ΔΔ G f = −3.8 ± 0.1 kJ/mol; Figure ).…”
Section: Introductionmentioning
confidence: 96%
“…We therefore asked whether it would have been possible to point them out as likely candidates beforehand. We calculated variant effects using two methods; structure based stabilities calculations using Rosetta and a direct coupling analysis (lbsDCA) of a multiple sequence alignment (MSA) of natural thioredoxins as such analyses have previously been shown to predict stability effects 22,30,31 (Figure 4). While both methods gave rise to reasonable overall Pearson correlations of 0.54 and 0.59 respectively, they failed to identify many of the substitutions which were inferred to be stabilizing (negative ΔΔG-values) in our GMMA.…”
Section: Resultsmentioning
confidence: 99%
“…More quantitative analyses have been enabled by a thermodynamic model that considers doubly substituted protein variants to infer the effect of single amino acid substitutions on both protein-protein interaction and folding free energies 18,19 , which was later shown to match chemical unfolding stabilities well 20 . We have recently used a folding sensor based on a bacterial heat shock response 21 to select for variants with improved thermodynamic stability of an already stable protein 22 . In line with this, we have shown that single substitution effects may be obtained by analysing the results of a DMS experiment with many diverse multiple-substituted protein variants, and suggested a global multi-mutant analysis (GMMA) for this task 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Even for systems with a lower dynamic range, it has previously been shown possible to identify stabilized protein variants 23 , 49 . In a recent study, the present reporter system has been used to successfully identify stabilized variants of the CI2 protein 50 .…”
Section: Discussionmentioning
confidence: 99%